Injury characteristics among Japanese international athletes: Report on the pre-competition medical check-up data of the Japanese Olympic Committee - Fukuda, N.; Hangai, M.; Hashimoto, R.; Nishida, Y.; Mizutani, Y.; Okuwaki, T.; Nakajima, K. (Cureus, 2024)
Introduction Injury trends among international athletes across sports remain underexplored in out-of-competition settings, particularly among Asians. The aim of this descriptive epidemiological study is to investigate the characteristics of injuries among Japanese international athletes during pre-competition medical check-ups from 2008 to 2019.